(3Pjd fRgI GdfXGQ aj bVGI GdCeUGQs - (3CMeO Hf eMeO Hf eMeO Hf YHO Gddg Hf CMeO GdQeGOjs
(3ChdgG (B:s
(3jbhd cGJHg CMeO Hf eMeO deG hbaJ Ydi fRgI GdfXGQ ai bVGI GdCeUGQ ddTjN GHf Gdedbf hQCjJg hUd ai Pdc Edi JQLeI bGVi GdbVGI Cf CVe Edi Pdc ef Sda ef bVGI eUQ s
(3BNQgG (B:s
(3ecJhH ajgG HNWg HYO GdMeO dI GdTQjYI PcQ bVGI GdOjGQ GdeUQjI ef Chd GdOhdi GdUdGMjI GdCjhHjI ai SfI GKfjf hSJjf hNeS eFI hEdi SfI SJjf hJeGfi eFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3hCdMbI HPcQ bVGI GdOjGQ GdeUQjI fbdgG ef ChQGb ceG dMb Hg fHPI ef bVGI eUQ HYO Cf UGQhG CQHYI Ydi GdePGgH hfRgI GdfXGQ dGHf Gdedbf GdhGOi BTi GdeJhai (B804(3g` HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN WdYI (B1836) s
Keywords: (3GdJGQjNs